MICROBIOLOGICAL ACTIVITY 1-CYCLOHEXYL-3-DIETHYLAMINOPROP-3-YN-1-YL ESTER OF N- PHENYL THIOCARBAMIC ACID - A. B. Bayeshov; А. K. Mamyrbekova; M. K. Kassymova; A. D. Mamitova; А. K. Mamyrbekova; N. U. Aliev; O. N. Chechina (Scientific Journal of Pedagogy and Economics, 2019)
This article is given the results of the synthesis of thiocarbamate aminoacetylene alcohol and tests of its microbiological activity against mushroom cultures - pathogens of root rot. It is established, an antimicrobial agent based on 1-cyclohexyl -3-diethylaminoprop-3-yn-1-yl ester of N-phenyl thiocarbamic acid has been given a significantly high protection effect from microbes at very low concentrations. The antimicrobial activity of the agent solution AN-60-2 was found to be from 10 to 100 times higher than the corresponding polytrimethylvinylethynylpiperidol (PTMVEP) solution. With the practical use of the drug AN-60-2, the economic effect can be achieved by increasing the safety of the seed pool, reduce crop losses from disease, in particular from root rot pathogens, during ventilation and during storage of agricultural products, reduce the cost sanitation of premises, boxes, securities, because they use very low doses of AN-60-2.